(untitled) (International Journal of Built Environment and Sustainability, 2022)
A significant increase in Covid-19 cases worldwide disrupted many sectors. The virus transmission through the air requires that people limit outdoor activities and apply social distancing. However, outdoor activities cannot be avoided because it is how people meet their daily needs. The urban landscape design arrangement is crucial, especially in public spaces. Old Town Semarang is a location with the potential for high outdoor activities, especially tourism. CCTV data shows that tourists could reach up to 500 people per day, and the average visitor does a comply with health protocols. This is worsened by the unadopted landscape conditions in this area to the current pandemic conditions. Therefore, a landscape design approach is needed to adapt to visitors’ needs and minimize virus transmission. This research examined the effect of landscape design on Covid-19 in the Old Town area. Data were collected on the existing landscape conditions, cultural heritage, and the distribution of positive Covid-19 cases and analyzed using spatial analysis, design simulation, and quantitative descriptive. The results were presented as simulation or landscape design recommendations according to cultural heritage elements and health protocols. The recommendations are a division of activity zones with a visitor quota system, and optimization of health facilities, signage for physical distance, as well as a clean and healthy lifestyle for visitors.